ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BIOLOGI BERKARAKTER KELAS XI SMA NEGERI UNTUK STANDARISASI RPP DI KOTA PADANG - Wahyuni, Yusri; Risdawati, Renny; Nerita, Siska (Pendidikan Biologi, 2013)
ABSTRACTÂ Lesson Plan (RPP) serves to streamline the learning process. To achieve that all teachers are expected to design a lesson plan (RPP) in accordance with the standards of Teacher Performance Assessment Instrument (IPKG). But in fact reality is just copying the teacher lesson in fact. The Teacher just coppied RPP from the old (KKG). RPP should fits with the character of local learners and RPP each semester has not been revised Â in accordence with the derelopment of science and tecnology. Therefore conducted an analysis of the RPP. The purpose of this rosgarel is to deternine the standarized lesson plans that mode by state high scool teachers. This research is descriptive wich collects RPP that made from state high shcool teachers in Padang city. Sampling technique is Stratified Random Sampling. Based on the research results obtained on the completeness of the components that is with an average of 67 % and that there are no 33 % and the results of the analysis of assessment instruments in the RPP desert city with an average value of 70 % with a fairly standard criteria. From the analysis and completeness of the components can be concluded that the RPP in the city of Padang has a fairly standard criteria .Â